A serious laugh. A few reflections on the role of humour, joke and laughter in the Galician political culture of the era of autonomy, with particular emphasis on the Galician Sejm - Szymczak, Damian (Laughter, humour, satire, 2024)
Satire, caricature, wit, and laughter are important elements of political culture, and can be employed in serious political struggles. Up to now, research on the role of laughter and humour in the political life of Galicia has been limited to the analysis of the press and literature and has been conducted primarily by literary historians. There has, as yet, been no analysis of the role of wit and laughter in the deliberations of the Diet of the Kingdom of Galicia and Lodomeria. This parliament was generally regarded as serious and even boring, yet there was no shortage of laughter. Moreover, it played an important role as a political weapon. The ability to use witticisms and to ridicule political opponents in the chamber of the Galician diet was highly valued. This paper represents an examination of this phenomenon and will propose a new research agenda.